Computing voxelised representations of macromolecular surfaces: A parallel approach. (May 2018) - Daberdaku, Sebastian; Ferrari, Carlo
Voxel-based representations of surfaces have received a lot of interest in bioinformatics and computational biology as a simple and effective way of representing geometrical and physicochemical properties of proteins and other biomolecules. Processing such surfaces for large molecules can be challenging, as space-demanding data structures with associated high computational costs are required. In this paper, we present a methodology for the fast computation of voxelised macromolecular surface representations (namely the van der Waals, solvent-accessible and solvent-excluded surfaces). The proposed method implements a spatial slicing procedure on top of compact data structures to efficiently calculate the three molecular surface representations at high-resolutions, in parallel. The spatial slicing protocol ensures a balanced workload distribution and allows the computation of the solvent-excluded surface with minimal synchronisation and communication between processes. This is achieved by adapting a multi-step region-growing EDT algorithm. At each step, distance values are first calculated independently for every slice, then, a small portion of the borders' information is exchanged between adjacent slices. Very little process communication is also required in the pocket detection procedure, where the algorithm distinguishes surface portions belonging to solvent-accessible pockets from cavities buried inside the molecule. Experimental results are presented to validate the proposed approach.